TLR4 activation by lipopolysaccharide confers survival advantage to growth factor deprived prostate cancer cells - Jain, Sumeet; Suklabaidya, Sujit; Das, Biswajit; Raghav, Sunil K.; Batra, Surinder K.; Senapati, Shantibhusan (The Prostate, 2015)
BACKGROUND Prostate cancer (PCa) cells express Toll‐like receptor‐4 (TLR4), a known pro‐tumorigenic molecule for different cancer cells. The cancer cells residing in the avascular region of the tumor confront various metabolic stresses and continuously adapt mechanisms to overcome them. We hypothesized that TLR4 activation might provide direct survival advantage to metabolically stressed PCa cells. METHODS We first investigated the effect of LPS on survival of serum deprived PCa cells. To understand the molecular mechanisms involved in TLR4 mediated PCa survival, we next investigated change in expression of markers for apoptosis, senescence and autophagy. Ultimately, the effect of LPS on established prostate tumors was confirmed in vivo using a syngeneic rat model for PCa. RESULTS Lipopolysaccharide (LPS)‐mediated TLR4 activation significantly enhanced survival of serum deprived (SD) PC3, DU145 and MAT‐LyLu PCa cells. TLR4 inhibition by a specific inhibitor resulted in rapid death of SD‐PC3 cells, which was significantly suppressed by LPS. Interestingly, LPS treatment suppressed macroautophagy in SD‐PC3 cells and increased expression of CCL2 (C–C motif ligand‐2), a known autophagy inhibitor and pro‐survival factor. Intra‐tumor LPS injection resulted in increased tumor mass, induced TLR4 activation, suppressed autophagy, and increased the macrophage population in MAT‐LyLu‐tumors. CONCLUSIONS Our study reveals that bacterial LPS enhance survival of PCa cells under conditions of nutrient stress through TLR4 activation. Moreover, LPS induces overexpression of CCL2 involved in the suppression of starvation‐induced macroautophagy in PCa cells, and enhanced macrophage population in prostate tumors in vivo. Taken together, the current study suggests the importance of bacterial infection or TLR4‐activation in prostate cancer pathogenesis. Prostate 75:1020–1033, 2015. © 2015 Wiley Periodicals, Inc.